DART-BIO: Modelling the interplay of food, feed and fuels in a global CGE model - Alvaro Calzadilla; Ruth Delzeit; Gernot Klepper (Kiel Institute for the World Economy (IfW), 2014)
Land use and land use change are determined as much by economic and institutional drivers as they depend on bio-physical conditions. Future pathways of socio-economic and environmental systems can only be assessed with scenarios which describe possible future paths of development. For this numeric models are one important tool. To capture the complex interactions between the development of regionally differentiated economic drivers, computable general equilibrium (CGE) models can be used. We discuss in a transparent way the inclusion of land and the representation of the complex agricultural production activities into DART-BIO, a CGE model. Implementing a scenario of changes in the preferences for meat and dairy products which is currently taking place in Asia, we find that these preference changes have only minor impacts on global agricultural prices while affecting regional production and trade. Results strongly depend on key parameter settings and highlight the importance of interlinkages between biofuel and livestock production.
Keywords: C61; Q16; Q42; 330; CGE Model; land use; biofuels; simulation model